2008
DOI: 10.1074/jbc.m707319200
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatase PHLPP Controls the Cellular Levels of Protein Kinase C

Abstract: The life cycle of protein kinase C (PKC) is controlled by multiple phosphorylation and dephosphorylation steps. The maturation of PKC requires three ordered phosphorylations, one at the activation loop and two at COOH-terminal sites, the turn motif and the hydrophobic motif, to yield a stable and signalingcompetent enzyme. Dephosphorylation of the enzyme leads to protein degradation. We have recently discovered a novel family of protein phosphatases named PH domain leucine-rich repeat protein phosphatase (PHLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
207
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(211 citation statements)
references
References 35 publications
3
207
0
1
Order By: Relevance
“…1A function of PHLPP, we confirmed that lack of PHLPP1 resulted in increased steady-state levels of PKCα (PKCα panel; see ref. 38, which shows that phosphorylation increases the stability of PKC isozymes); reintroduction of PHLPP1β decreased the steady-state levels of PKCα in a manner that depended on the catalytic activity and presence of the PH domain (which is required for PHLPP to recognize PKC in cells) but not in the presence of the PDZ ligand (which is not required for PHLPP to recognize PKC in cells) (38). These data reveal that PHLPP1 suppresses the steady-state levels of the EGFR by a mechanism depending on its catalytic activity and an intact LRR segment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A function of PHLPP, we confirmed that lack of PHLPP1 resulted in increased steady-state levels of PKCα (PKCα panel; see ref. 38, which shows that phosphorylation increases the stability of PKC isozymes); reintroduction of PHLPP1β decreased the steady-state levels of PKCα in a manner that depended on the catalytic activity and presence of the PH domain (which is required for PHLPP to recognize PKC in cells) but not in the presence of the PDZ ligand (which is not required for PHLPP to recognize PKC in cells) (38). These data reveal that PHLPP1 suppresses the steady-state levels of the EGFR by a mechanism depending on its catalytic activity and an intact LRR segment.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have established that PHLPP1 and PHLPP2 suppress oncogenic signaling by at least two mechanisms (reviewed in ref. 37): (i) direct dephosphorylation and inactivation of the prosurvival kinase AKT, PKC (38), and S6 kinase (39), and (ii) direct dephosphorylation and activation of the proapoptotic kinase Mst1 (40). Whether additional mechanisms account for the tumor-suppressive function of PHLPP is largely unexplored.…”
mentioning
confidence: 99%
“…Dephosphorylation of PKCs in cells was initially shown to be sensitive to okadaic acid, which implicated the PP2a-like phosphatases in this process [79,80,75]. More recent studies have identified an additional family of okadaic acidinsensitive phosphatases called PHLPPs that specifically dephosphorylate the HM (but not the TM) of PKCs upon prolonged phorbol ester treatment [81]. It should be noted however that while dephosphorylation serves as an important switch to turn off the activity of these enzymes, dephosphorylation does not necessarily predispose the enzyme to degradation [79].…”
Section: Dephosphorylation Of Pkcmentioning
confidence: 99%
“…20 In addition, both PHLPP1 and PHLPP2 have been shown to dephosphorylate PKCa and PKCbII, whereas PHLPP1 has also been implicated in the negative regulation of the Ras/Raf/MEK/ERK pathway. 22,23 Recently, several lines of evidence have suggested that PHLPP1 and PHLPP2 are involved in the pathogenesis of various types of cancer. Reduced or absent expression of PHLPP1 and PHLPP2 has been reported in approximately 80% of primary colorectal cancer specimen.…”
Section: Introductionmentioning
confidence: 99%